A Quantitative Study on the Effect of Waste Management and Handling Plans on Marine Pollution in MV. Zaleha Fitrat - Ikhlasul Amal; Haryani Haryani; BL. Hentri Widodo; Retno Indriyati; Haris Padilah (JURNAL BARTEK, 2025)
Marine pollution due to shipping activities is a pressing environmental issue, particularly related to waste management on board ships. This study aims to analyze the influence of the Garbage Management Plan (GMP) and waste handling on the level of marine pollution on the MV Zaleha Fitrat. Using a descriptive quantitative approach, data were obtained through a survey of 23 crew members using a questionnaire covering GMP implementation, waste handling, and perceptions of marine pollution. The results showed that the implementation of GMP and waste handling were mainly in the high category, at 56.52% and 52.17%, respectively. Meanwhile, the level of marine pollution perceived by the crew was mainly in the low category (60.87%). These findings indicate that proper implementation of GMP and proper waste handling procedures can reduce the level of marine pollution. Therefore, improving crew understanding and monitoring the implementation of waste management procedures are key to mitigating marine pollution in the shipping sector.